Territorio e turismo: un lungo dialogo Il modello di specializzazione turistica di Montecatini Terme - Romei, Patrizia (Strumenti per la didattica e la ricerca, 2016)
Tourism is a driving sector of the world economy. Tourist activities interact directly with the economic, social and ecosystemic dimension of the territories, producing intense territorial relationships characterised by a strong local-global link. To deal with the intrinsic complexity of each territorial analysis, a multiscalar (local, regional, national, European, global), multitemporal (long, medium, short term) and multidimensional (economic, social, environmental) study methodology has been chosen. The common thread runs around the examination of a pioneering tourist destination whose history has been intertwined with the birth and expansion of tourism: Montecatini Terme. The aim is to outline a tourism specialisation model starting from the territorial relationships that have marked its history, landscape, culture and oriented economic development. A model that has evolved, partly anticipating and partly following global and European dynamics.